Analisis Variasi Diameter Pulley Mesin Sangrai Kemiri Semi Otomatis terhadap Kualitas Hasil Sangrai Kemiri - Darmawan, Indra; Sakti, Arya Mahendra; Utama, Firman Yasa; Abdi, Ferly Isnomo (Jurnal Rekayasa Mesin, 2023)
Candlenut is a shrub with broad leaves that produces edible fruit that can also be used as an ingredient in various foods and cosmetics. Various studies on the method of roasting biji kemiri seeds have been carried out, but research on modification of the pulley for the candlenut roasting machine is still lacking. Therefore, it is necessary to conduct research on the effect of changing the diameter of the pulley on the candlenut roasting machine to determine the effect on the results of roasting the candlenut seeds. A quantitative technique was adopted as the research methodology. The object of research used in this study were pulleys with different diameters on Lumajang black sand media which were processed for 15 minutes, with a diameter of 3, 4 or 5 inches. It was concluded that the best variation of the pulley diameter to use is the 4-inch diameter because it produces a rotation of 602.5 RPM when roasting the biji kemiris with an electric motor that has a rotation of 2800. The results obtained from a 3-inch diameter produce a quality of 1.73% moisture content, then a 4-inch diameter produces a quality of 1.71% moisture content, and a 5-inch diameter produces a moisture content of 1.69%.